2021
DOI: 10.1002/ajs4.181
|View full text |Cite
|
Sign up to set email alerts
|

Carers’ experiences of the National Disability Insurance Scheme workforce: A qualitative study informing workforce development

Abstract: The Australian National Disability Insurance Scheme (NDIS) requires a skilled workforce capable of assessing the diverse needs of service participants and providing tailored services accordingly. There is currently

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Instead, Australia has seen an uptick in guardianship applications and financial management orders [ 60 ]. Additionally, carers of people with disabilities report that the NDIA/Local Area Coordinators (LAC) staff have inadequate levels of understanding of disability and do not have the requisite empathy and compassion that would ameliorate this inexperience [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, Australia has seen an uptick in guardianship applications and financial management orders [ 60 ]. Additionally, carers of people with disabilities report that the NDIA/Local Area Coordinators (LAC) staff have inadequate levels of understanding of disability and do not have the requisite empathy and compassion that would ameliorate this inexperience [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Informal supports describe extensive difficulties negotiating with NDIA [ 34 ]. LACs and planners have been described as judgmental, dismissive, and possessing limited capabilities to work collaboratively with informal supports of NDIS participants [ 74 ]. As part of the NDIS process, carers are often excluded from planning meetings, resulting in unmet participant support needs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the workforce has increased in size over the last 10 years, reports and evaluations of the NDIS implementation 20,21 and the disability services workforce [22][23][24] show that the workforce is struggling to meet community service demand in a changing policy environment. Literature reviews by Gilroy et al 12 and Trounson et al 21 reported that the disability services sector needs an Aboriginal and Torres Strait Islander designed and managed workforce strategy, which must include a cultural safety model underpinned by community-based rehabilitation principles.…”
Section: What Is Already Known On This Subjectmentioning
confidence: 99%